Relapsing polychondritis: a clinical review for rheumatologists. (6th November 2017) - Kingdon, Jack; Roscamp, Joseph; Sangle, Shirish; D'Cruz, David
Abstract: Relapsing polychondritis (RPC) is a rare autoimmune rheumatic disorder that is traditionally classified as a systemic vasculitis. It is characterized by inflammation of cartilage, and typical presenting features include chondritis of the nasal bridge, auricular chondritis, ocular inflammation and involvement of the bronchial tree. Its rarity often leads to considerable delay in establishing a diagnosis and poses a significant management challenge to clinicians, as no conventional guidelines exist. This review summarizes the clinical features of RPC and provides guidance for rheumatologists on making the diagnosis and assessing organ involvement. The current state of RPC management is reviewed, with a focus on the use of the anti-TNF-α agents in patients with pulmonary involvement, the leading cause of mortality and morbidity in RPC.